Identification and comparison of the volatile constituents of fresh and dried leaves of Spondias mombin found in North-central Nigeria: in vitro evaluation of their cytotoxic and antioxidant activities - Oladimeji, Abdulkabir Oladele; Aliyu, Medinat Bola; Ogundajo, Akintayo Lanre; Babatunde, Oluwatoyin; Adeniran, Oluremi Ishola; Balogun, Olaoye Solomon (Taylor & Francis publishing, 2023)
Pharmaceutical biology, 4 pages